2005
DOI: 10.1242/jcs.02581
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome architecture in the decondensing human sperm nucleus

Abstract: Whereas recent studies demonstrated a well-defined nuclear architecture in human sperm nuclei, little is known about the mode of DNA compaction above the elementary structural unit of nucleoprotamine toroids. Here, using fluorescence in-situ hybridization (FISH) with arm-specific DNA probes of chromosomes 1, 2 and 5, we visualized arm domains and established hierarchical levels of sperm chromatin structures. The compact chromosome territories, which in sperm have a preferred intranuclear localization, have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 73 publications
9
103
3
Order By: Relevance
“…Usually, telomeres are evenly distributed in mammalian cell nuclei; however, in some cell types (e.g., sperm), they are preferentially located in the nuclear periphery (Mudrak et al 2005). In our study, we observed no changes in the number or distribution of telomeres when MSCs and mature adipocytes were compared.…”
Section: Discussioncontrasting
confidence: 66%
“…Usually, telomeres are evenly distributed in mammalian cell nuclei; however, in some cell types (e.g., sperm), they are preferentially located in the nuclear periphery (Mudrak et al 2005). In our study, we observed no changes in the number or distribution of telomeres when MSCs and mature adipocytes were compared.…”
Section: Discussioncontrasting
confidence: 66%
“…Protocol B: The cell suspension was fixed with 0.05% paraformaldehyde in PBS, decondensed with 10 mM DTT and 0.5 mg/ml heparin for 30 min (Mudrak et al, 2005), smeared onto slides, and air-dried. The cells were washed 3 times in PBS and incubated with primary and secondary antibodies, as done in Protocol A.…”
Section: Immunochemistrymentioning
confidence: 99%
“…Before immunochemistry, testis cells or mature sperm were prefixed with 0.05% paraformaldehyde in PBS and decondensed with 10 mM DTT and 0.5 mg/ml heparin for 30 min (Mudrak et al, 2005). Alternatively, the cells were decondensed with 10 mmol/L DTT and 4 mmol/L lithium diiodosalicylate (LIS) in 100 mmol/L Tris-HCl (pH 8.0) for 45 min (Wyrobek et al, 1990), airdried, and fixed with 100% cold methanol.…”
Section: Chemically Induced Chromatin Decondensationmentioning
confidence: 99%
“…Indeed, in human sperm, chromosomes occupy defined preferred intranuclear positions [7,10,38]. Paternal genome is activated early after fertilization, during S/G2 phase of the first cell cycle i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, chromosome topology in gametes and zygotes is poorly studied. Recent studies clearly demonstrated that chromosomes in mature human spermatozoa have nonrandom, well-defined, and unique spatial organization [5][6][7]. In addition, sperm chromosomes have a preferred intracellular positioning [8][9][10].…”
Section: Introductionmentioning
confidence: 99%